Drivers of sustainable financial Consumerism: Exploring the impact of artificial intelligence, finfluencers, financial literacy, and product quality on sustainable development - Ashutosh Dash; Giridhari Mohanta (Cleaner and Responsible Consumption, 2025)
Sustainable Financial Consumerism (SFC) encapsulates long-term financial well-being and social equity. Despite its critical importance, the interplay between various determinants of SFC particularly in alignment with the Sustainable Development Goals (SDGs), remains limited. This study fills a salient gap by employing structural equation model to explain the determinants of SFC, focusing on the exogenous variables such as financial literacy and awareness (FLA), artificial intelligence (AI), and financial product quality (FPQ). Utilizing the data collected from the rural households of selected aspirations districts in India, the study investigates the moderating effect of FLA in shaping SFC. By identifying financial literacy awareness as a direct influencer and a moderator, the findings offer actionable insights for stakeholders to design more targeted strategies for promoting sustainable financial practice and rational decision-making. The research highlights the potential of leveraging AI and social media to deliver personalized, engaging, and accessible financial education tailored to diverse demographics. Moreover, the study underscores the importance of collaboration among financial institutions, technology providers, and educational agencies to build an ecosystem that advances financial literacy (SDG 4), and promote sustainable financial behaviour for inclusive economic growth (SDG 8). Such multi-stakeholder partnerships also align with SDG 17 (Partnerships for the Goals), fostering synergies that enhances broader sustainability objectives.